Analysis of the GROW Coaching Model Program in Developing High-Performing Employees - Etty Erikawati; Hamsinah Hamsinah; Agustina Mogi (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2026)
This study aims to analyze the Coaching program and the implementation of the GROW conversation model (Goal, Reality, Options, and Will) at PT Bank Maybank Indonesia Tbk. as a human resource development strategy to enhance employee performance and develop high-performing employees. The program also serves as the Bank’s effort to foster adaptive and competitive talent capable of meeting the evolving demands of the banking industry. A qualitative approach with an ethnographic method was employed through direct observation, in-depth interviews, and source triangulation involving managerial informants and key informants from the Human Capital division. The findings indicate that the GROW-based Coaching program contributes to increased motivation, employee engagement, self-awareness, problem-solving capabilities, adaptability, and leadership readiness. However, the program's implementation continues to face challenges, including a limited number of qualified Internal Coaches, variations in coaches’ understanding and application of the GROW model, and a lack of an effective monitoring and evaluation system. To strengthen coaching outcomes, the study highlights the importance of integrating SMART Goal principles (Specific, Measurable, Achievable, Relevant, and Time-bound) into every stage of the GROW framework to ensure that coaching objectives are clear, measurable, and aligned with organizational goals. The study also reveals that psychological safety, particularly during the Reality stage, plays a critical role in fostering open communication and encouraging employees to identify solutions independently.